2007
DOI: 10.1111/j.1540-8175.2007.00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Live/Real Time Three‐Dimensional Transthoracic Echocardiographic Findings in Primary Left Atrial Leiomyosarcoma

Abstract: We describe an adult patient with a primary left atrial leiomyosarcoma in whom live/real time three-dimensional transthoracic echocardiography showed echolucent areas within the mass consistent with necrosis or hemorrhage surrounded by dense band-like echo densities indicative of fibrosis or collagen giving a "doughnut" like appearance. These findings were consistent with histopathology, which showed areas of necrosis and dilated vascular channels within the fibrotic tumor. Our case further illustrates the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…These areas corresponded to what was seen by histology after the mass was removed surgically (from Suwanjutah et al29 ) (reproduced with permission from Wiley-Blackwell). A left atrial leiomyosarcoma is shown by RT3DTTE.…”
mentioning
confidence: 52%
“…These areas corresponded to what was seen by histology after the mass was removed surgically (from Suwanjutah et al29 ) (reproduced with permission from Wiley-Blackwell). A left atrial leiomyosarcoma is shown by RT3DTTE.…”
mentioning
confidence: 52%
“…It also allows the manipulation of images in the space, obtaining views and planes, and aligning structures in ways that were impossible to get before with 2D imaging. Emphasis can then be put on the cardiac mass, providing a more comprehensive assessment of its inner structure, which correlates better with pathologic fi ndings (necrosis, hemorrhage, cystic areas, or fi brotic bands) [4,5].…”
Section: Unlimited Slicing and Croppingmentioning
confidence: 99%
“…A unique finding on live/real-time three-dimensional TTE of high-grade cardiac sarcomas described by Suwanjutah et al is the presence of the dense band like echo density which surrounds small echolucent areas imparting doughnut-like configuration 7. Moreover, this three-dimensional imaging modality is also helpful in evaluating the change in volume of cardiac tumours during the period of follow-up as the two-dimensional TTE may underestimate the volume by 20%–25% 7. Another study also concluded that three-dimensional echocardiography is ideal for determining the relationship of cardiac tumours with adjacent structures and the haemodynamic effects produced by them 8.…”
Section: Discussionmentioning
confidence: 99%
“…TTE is the method of choice for evaluating cardiac tumours and provides important morphological and functional information of the heart 7. A unique finding on live/real-time three-dimensional TTE of high-grade cardiac sarcomas described by Suwanjutah et al is the presence of the dense band like echo density which surrounds small echolucent areas imparting doughnut-like configuration 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation